(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2016)
While deriving the magnetic energy solution an explanation of mass and an explanation of charge were found. Also a reason for failure to find a magnetic monopole was given. It was found that all known particles can be accounted for by calculating the mass using a formula given in this solution. Also many new particles were found. The spherical harmonics were generated giving the known orbitals. Spin wasproposed to be a magnetic dipole. The mass of the electron was found to be related to the fine structure constant by 13.6*2*137*137 = 510,516.8ev where511Kev is accepted. The reason that the electron does not enter the nucleus was found.